2012
DOI: 10.4209/aaqr.2012.03.0060
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hydrogen Sulfide by Iron-Rich Soil: Application of the Deactivation Kinetic Model for Fitting Breakthrough Curve

Abstract: In this study a deactivation kinetic model was used to predict the breakthrough curve in a noncatalytic gas-solid reaction. The iron-rich soil was tested to react with H 2 S under a reducing atmosphere at high temperature. The results indicated that the deactivation kinetic model can be well fitted to the breakthrough curve in the experimental range. The breakthrough curves were accurately predicted by the model, and provide useful information for the time to reload the solid materials in the reaction. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…To date, plentiful processes have been developed for H 2 S removal, and many new, effective methods will appear in the near future (Ma et al, 2009;de Angelis et al, 2010;Ko and Hsueh, 2012;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, plentiful processes have been developed for H 2 S removal, and many new, effective methods will appear in the near future (Ma et al, 2009;de Angelis et al, 2010;Ko and Hsueh, 2012;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, H 2 S from coal derived natural gas has been effectively removed by iron-rich and zinc contaminated soils (Ko, 2008(Ko, , 2011Ko and Hsueh, 2012). Moreover, cow manure compost in biofilter columns has shown considerable potential for H 2 S removal, albeit through oxidation as well as precipitation (Zicari, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…is shortcoming of use of diluted oxygen leads to a long-time regeneration reaction. In the past, we have investigated a series of laterites on the application of high-temperature desulfurization, and the results indicated that laterites are the potential material for high-temperature desulfurization [7,8].…”
Section: Introductionmentioning
confidence: 99%